Role of the GPR55 receptor in the modulation of joint afferent mechanosensitivity - Paton, Kenneth (2015)
Deep somatic pain originating from synovial joints is a major clinical problem as it is the primary reason for loss of joint mobility and function in musculoskeletal disorders. Musculoskeletal disorders, including osteoarthritis (OA), are the most prevalent cause of disability worldwide with an estimated 1 in 3 adults affected. Current therapies for the treatment of joint pain have limited effectiveness and certain drugs produce unwanted side effects, preventing their long-term use. Targeting pain at the level of the joint may have the potential to maximise treatment efficacy, whilst reducing possible non- specific side effects associated with systemic drug treatment. Identification of novel analgesic targets that inhibit peripheral mechanical sensitization during joint pain states will be critical to the development of improved analgesics for these conditions. Based on recent preclinical findings, the orphan G protein- coupled receptor GPR55 has controversially been suggested to be the novel third cannabinoid receptor and has been identified as a potential novel target for the treatment of pain. Very few studies have investigated the effects of GPR55 activation on nociceptive processing in vivo and only one at the level of the joint during acute inflammatory arthritis. The aim of this thesis was to investigate the role of GPR55 in the modulation of joint afferent mechanosensitivity in vivo, and whether this role is altered in an experimental model of OA during established pain.